In vitro released antigens in diagnosis and immunomonitoring of filaria and tuberculosis - Harinath, B. C. (Springer India, 1997)
In vitro released antigens by living parasites or bacteria underin vitro maintenance or short term culture showing specific humoral immune response have been explored in development of immunodiagnostics for infectious diseases such as filariasis and tuberculosis in our laboratory. ELISA usingB. malayi mf ES antigen has been explored for detecting IgG antibody by Indirect ELISA and antigen by Inhibition ELISA and in immunomonitoring of carriers as well as clinical filarial cases. A ten year follow up of mf carriers with DEC therapy showed disapperance of antigen and antibody followed by reappearance in few cases in an endemic area. None of the cases followed developed clinical symptoms suggesting the need for long term monitoring and treatment of microfilaraemic carriers. Further immunomonitoring was found to be useful in confirming filaria aetiology in the absence of microfilaremia and determining appropriate period of treatment of acute, early clinical and occult filarial infections for clinical relief and cure. Indirect Stick Penicillinase ELISA system using Mtb EST-6 antigen for detecting tuberculous IgG antibody and a Sandwich Penicillinase ELISA system using affinity purified antibody for detecting circulating antigen were explored in tuberculosis. A combination of both the assay systems with a sensitivity of 70% and specificity of 98% was found to be promising in the precise diagnosis of pulmonary tuberculosis. Further antigen detection was found to be useful in bone and joint tuberculosis.